The Battle of the first Zagar valley in Ain Kashra saturday 11shawal 1376h /11 May1957 - kouicem, Mohammed (The Algerian Historical Journal, 2026)
North Qasantina Region recognized hundreds battles during Great Algerian Revolution (1954-1962), skikda state actualy the second Nahia(1954-1956) than the third Mintaka(1956-1962)there were 40 battles, such as the first Zagar valley battle in11May1957. This research paper study this battle according to historical method causes thane vents than results, in order to present the real jihad of Algerian to get back our independence than to make victory in development battle by scientific progress